Buḥrān va najāt : chih gūnah sūʼ-i idārah dar mamlikat buḥrān paydā kard va jāmiʻah-ʼi dūzdān az mawqaʻ istafādah kardah . - Muḥī al-Dīn (Maṭbaʻah-i Anīs, 1990)
Historical study of Afghanistan, chiefly political during 19th and early 20th century.